Assessment of Knowledge among Nurses Regarding Spread of Nosocomial Infection - Zoya Nazeer, Arusa Bano, Rubina Naz, Muhammad Ahmed Sohail, Muhammad Asim Amin (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Nosocomial infections, also described as healthcare-associated infections (HAI), are illnesses that occur in hospitals or other healthcare settings. Infection obtained while receiving care and was not aware at the moment of hospitalization. Hospital - associated infection occurs when a client is taken to a hospital for a long or short term for particular treatment reasons but has no indication of infection time of admission. Nosocomial infections can always be microbial, prion, highly infectious, or parasitic, but they can be observed with in wind, inside the body, or on surfaces.(1) Objective: To assess the knowledge among nurses regarding spread of nosocomial infection. To identify association between knowledge about nosocomial infection and demographic variables of staff nurses. Place and duration: University Lahore teaching hospital Lahore, Pakistan. This study approximately took in 5 months (September, 2021 to January, 2022). The data is collected in 1 month. Methodology: A cross sectional study design was used in of University Lahore teaching hospital Lahore, Pakistan. Questionnaire distributed among staff nurses and data analyzed by SPSS software (version 21). All male and female Staff nurses having age20-60 years, who have more than one year working experience were included. Sample size of n=159 staff nurses were taken by using convenient sampling. Throughout the study, participants’ identities were kept strictly confidential to ensure research participants protection. Results: The results of study show that 23.9% of individuals demonstrated excellent knowledge of nosocomial infection transmission. 46.5 percent of individuals had good knowledge about nosocomial infection spread, whereas 29.6 percent had poor knowledge about nosocomial infection spread. Conclusion: We concluded that nurses had a good knowledge regarding spread of nosocomial infection. Antibiotic resistance in emerging pathogens can be reduced by following sound and health care delivery techniques devised by infection control committees, preventing transmission of these illnesses with suitable antimicrobial usage methods. Keywords: Knowledge, nurses, nosocomial infection